Dependence of average total kinetic energy of fission fragments on excitation energy of fissioning nucleus - V.Yu. Denisov; I.Yu. Sedykh (Physics Letters B, 2022)
The expression of dependence of the average total kinetic energy of fission fragments on the excitation energy of the fissioning system is obtained in a simple model, which takes into account the statistical and quantum properties. The experimental data of the average total kinetic energy of fragments formed in the fission of nuclei 234,236,239U and 240Pu are well described using the obtained expression in the wide range of the excitation energy of these nuclei. The origin of the energy dependence of the average total kinetic energy is discussed in details.